Energy Storage Applications in Power Systems - Wang, Zongjie; Younesi, Abdollah (IntechOpen, 2023)
As the world strides toward a renewable energy future, the role of energy storage systems in power infrastructures has never been more pivotal. Energy Storage Applications in Power Systems is an in-depth exploration of the exciting advancements in this field. This comprehensive resource covers a broad spectrum of topics and meticulously unites the various aspects of energy storage technologies and their real-world applications. From mechanical to superconducting magnetic energy storage systems, the book offers a deep understanding of different technologies, their unique characteristics, and their potential in enhancing power quality and system stability. Further, it extends its discourse to applications at multiple scales: from the residential to neighborhood level, illustrating how energy storage systems can transform power systems and foster a community-centric energy ecosystem. The book also investigates the balancing act between renewable energy capacity, time-of-use tariffs, and energy storage. These discussions provide insights into the broader implications of energy storage, underscoring its significance in optimizing energy utilization, reducing costs, and enhancing grid reliability. Above all, this volume serves as a vital reference for a wide-ranging audience, including researchers keen on exploring new scientific avenues, academics educating the next generation, industry practitioners implementing these technologies, and policymakers shaping our energy future. It aims to inspire innovative solutions and propel us toward a sustainable and resilient power landscape. The knowledge encapsulated within these pages provides both a testament to the progress we have made and a roadmap for the journey ahead in the realm of energy storage applications in power systems. Through a blend of rigorous science and practical application, this book stands as an indispensable guide, lighting the path toward our sustainable energy future.